Advances in Electrospinning of Natural Biomaterials for Wound Dressing. (27th March 2020) - Wang, Fadong; Hu, Shui; Jia, Qingxiu; Zhang, Liqun
Abstract : Electrospinning has been recognized as an efficient technique for the fabrication of polymer nanofibers. Various polymers have been successfully electrospun into ultrafine fibers in recent years. These electrospun biopolymer nanofibers have potential applications for wound dressing based upon their unique properties. In this paper, a comprehensive review is presented on the researches and developments related to electrospun biopolymer nanofibers including processing, structure and property, characterization, and applications. Information of those polymers together with their processing condition for electrospinning of ultrafine fibers has been summarized in the paper. The application of electrospun natural biopolymer fibers in wound dressings was specifically discussed. Other issues regarding the technology limitations, research challenges, and future trends are also discussed.